Geochemical evaluation of land use at a medieval harbor site in Masuda City, Chugoku region, Japan - Banzragch, Dalai; Ishiga, Hiroaki; Nasandulam, Damdinpurev (Proceedings of the Mongolian Academy of Sciences, 2019)
A large-scale Medieval harbor site has been recently discovered at Nakazu-Higashihara in Masuda City, Chugoku region, Japan. The Medieval harbor site is divided into north and south areas. The concentration of 22 elements in soil samples from the north of the harbor site was determined in order to identify the geochemical signatures of the Medieval harbor site. The evidence described in the north area is an example of identification of both natural and anthropogenic processes that lead to geochemical variations within the archaeological soils. The north area of the site contains silt and sandy soils characterized by highest concentration of Zr and relatively low levels of most other elements (except for Sr and TS). Negative or weak positive correlations between TiO2 and MnO, and CaO and P2O5 in the north area indicate that this association of elements represents an ancient anthropogenic signature, especially related to residential sites in all soil types. Correlation between TiO2 and Ni, Y, Nb, Zr, Th, and Fe2O3 did not reflect the anthropogenic history. However, these elements and their ratios can be used to identify sources, as well as to establish baseline concentration of other elements which are influenced by anthropogenic and detrital inputs.